Comparison on Adhesion Control Performance for the New Generation ElectricLocomotive Made in China and Toshiba 19E Electric Locomotive Made in Japan - QIU Zirong; ZHANG Zhengfang; LIANG Xingyuan (机车电传动)
The adhesion control technical level of the new generation electric locomotive made in China represented by Shenhua and20E locomotive for South Africa was introduced. Aiming at the traction requirement, adhesion utilization control software for Shenhua and20E electric locomotive was improved, and adhesion control strategies based on direct control of adhesion force and differential accelerationadhesion control strategy were offered. The experiment data and acceptance procedure was provided. By the comparison with Toshiba 19Eelectric locomotive, the performance of Shenhua and 20E electric locomotive adhesion control software was proved reached advanced level.